The mutational landscape of the SCAN‐B real‐world primary breast cancer transcriptome - Christian Brueffer; Sergii Gladchuk; Christof Winter; Johan Vallon‐Christersson; Cecilia Hegardt; Jari Häkkinen; Anthony M George; Yilun Chen; Anna Ehinger; Christer Larsson; Niklas Loman; Martin Malmberg; et al. (EMBO Molecular Medicine, 2020)
Abstract Breast cancer is a disease of genomic alterations, of which the panorama of somatic mutations and how these relate to subtypes and therapy response is incompletely understood. Within SCAN‐B ( ClinicalTrials.gov : NCT02306096), a prospective study elucidating the transcriptomic profiles for thousands of breast cancers, we developed a RNA‐seq pipeline for detection of SNVs/indels and profiled a real‐world cohort of 3,217 breast tumors. We describe the mutational landscape of primary breast cancer viewed through the transcriptome of a large population‐based cohort and relate it to patient survival. We demonstrate that RNA‐seq can be used to call mutations in genes such as PIK3CA, TP53, and ERBB2, as well as the status of molecular pathways and mutational burden, and identify potentially druggable mutations in 86.8% of tumors. To make this rich dataset available for the research community, we developed an open source web application, the SCAN‐B MutationExplorer ( http://oncogenomics.bmc.lu.se/MutationExplorer ). These results add another dimension to the use of RNA‐seq as a clinical tool, where both gene expression‐ and mutation‐based biomarkers can be interrogated in real‐time within 1 week of tumor sampling.